Study of Al-Quran Verses and the Success of Philanthropic Communities on Social Media - Nasution, Muhammad Ali Azmi; Rusiana; Eztika Azzahra; Rahma Wita (Yayasan Salam Cerdas Al-Fattah, 2024)
Aspects of Islamic philanthropy include zakat, infaq, alms and waqf. The development of technology is an easy way to promote philanthropic activities on social media by making it easier for people to access them. It is inevitable that social media extensions bring lifestyle changes to humans. In the Philonthropic Movement, activities focus on volunteering and providing assistance or providing voluntary services as a form of caring. This research is library research with thematic methods. Research shows that a philonthropic community needs community support to join in activities to achieve the goals of the social activity program. Efforts to optimize the network of donors on social media, but also related to the realization of programs that are more varied, educational and creative in collecting donations and distributing donations. Although the context of the realization of distribution of donations is mostly distributed in the form of charity and has not been optimized for community empowerment programs. So the basic needs of the poor require faster distribution of donations, such as educational assistance, basic food assistance, and so on. Philanthropy in the Qur'an is not only a religiously motivated charity movement, but also as a form of humanity to care for one another.